2021
DOI: 10.3390/met11101633
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Mechanical Properties and Corrosion Behavior of the Aluminum Alloy Components Repaired by Cold Spray with Al-Based Powders

Abstract: Aluminum alloy components of high-speed trains have a great risk of being corroded by various corrosive medium due to extremely complex atmospheric environments. This will bring out huge losses and reduce the safety and stability of trains. In order to solve the problem, cold spray process was used for repairing the damage of the aluminum alloy components with Al-based powders. Microstructure, mechanical properties and corrosion behavior were studied. The results indicated that there were very few pores and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It was found that the addition of Al 2 O 3 solid particles to pure aluminum powder in certain proportions improved the mechanical properties of obtained coatings [15][16][17]. Thus, in [18] it was determined that with the addition of Al 2 O 3 particles, the bond strength of the coating with the magnesium substrate increased. The increase in microhardness and wear resistance of coatings was also observed.…”
Section: Introductionmentioning
confidence: 97%
“…It was found that the addition of Al 2 O 3 solid particles to pure aluminum powder in certain proportions improved the mechanical properties of obtained coatings [15][16][17]. Thus, in [18] it was determined that with the addition of Al 2 O 3 particles, the bond strength of the coating with the magnesium substrate increased. The increase in microhardness and wear resistance of coatings was also observed.…”
Section: Introductionmentioning
confidence: 97%